Essential oil content and its composition in herb of lemon balm (Melissa officinalis L.) breeding strains. Issue 4 (4th July 2017) - Seidler-Łożykowska, Katarzyna; Zawirska-Wojtasiak, Renata; Wojtowicz, Elżbieta; Bocianowski, Jan
Abstract: The evaluation of essential oil content and its composition in the herb of lemon balm breeding strains was the goal of the research, with the aim of selecting appropriate genotypes for further breeding programs. In 2013–2014, at the beginning of flowering, the herb was collected from ten randomly selected plants of eight strains bred in the nursery. The essential oil content was estimated after hydrodistillation of dried lemon balm herb, in accordance with the method recommended by the European Pharmacopoeia VI; the essential oil was then subjected to gas chromatography. Both the yield of lemon balm essential oil and its composition showed significant differentiation among the investigated strains. These differences were associated with fluctuations in weather conditions in the years of the research. Higher levels of the main components (neral and geranial), though not of essential oil itself, were observed under higher insolation.